Self-Administration of Vecuronium by a Medical Student: An Autopsy Case Report - Mukul Sharma; Biplab Rath; Naveen A; Manas Ranjan Sahu (Indian Journal of Forensic Medicine & Toxicology, 2021)
During COVID-19 pandemic the frontline healthcare workers have been at risk the most. Long workinghours, emotional stress from not seeing families for days together takes a toll on the psychological wellbeingof a person. This leads to increase incidence of self-harm amongst the individuals. Vecuroniumbromide is a muscle relaxant, easy availability of such drugs amongst the medical professionals is a matterof great concern. Monitoring and cautious dispensing of them should be done. Here we report a case ofself-administration of vecuronium by a medical student .The purpose of documenting this case is to createawareness among healthcare workers to keep a watch on mental health of fellow colleagues. Psychologicalsupport groups in medical college hospitals are the need of hour.